A Study on Problems Faced by the Retail Stores in Coimbatore City - Dhanabkakyam, M.; Shanthi, A. (Gyan Management Journal, 2009)
Retailing involves a direct interface with the customers and the coordination of business activities from end to end - right from the concept or design stage of a product offering to its pre and post-delivery services to the customer. The industry has to contribute the economic growth o many countries and it is undoubtedly one of the fastest changing and dynamic industries in the world. This study wa1 conducted with the objective to analyse the factors affecting day to day operation and problems faced by the retail store in Coimbatore city. Chi-square test and Average ranking analysis were used far analyzing the data. Primary data were collected from the 75 retail stores by using interview schedules. It was concluded that the retailers must constantly update their knowledge of the retail environment to survive. Retailers have to maintain cordial relationship with their suppliers and customers.
Keywords: Retail stores; Coimbatore city